2020
DOI: 10.3389/fonc.2020.00928
|View full text |Cite
|
Sign up to set email alerts
|

A Potential Role of YAP/TAZ in the Interplay Between Metastasis and Metabolic Alterations

Abstract: Yes-Associated Protein (YAP) and Transcriptional Co-activator with PDZ-binding Motif (TAZ) are the downstream effectors of the Hippo signaling pathway that play a crucial role in various aspects of cancer progression including metastasis. Metastasis is the multistep process of disseminating cancer cells in a body and responsible for the majority of cancer-related death. Emerging evidence has shown that cancer cells reprogram their metabolism to gain proliferation, invasion, migration, and anti-apoptotic abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 192 publications
(253 reference statements)
2
66
0
Order By: Relevance
“…Most cells use membrane trafficking to continually rework their plasma membrane through ruffles, folds, endoand exocytosis, and it has been suggested that cells sense and regulate their volume and surface area through plasma membrane tension (73) . Recent evidence suggests that plasma membrane domains such clathrin coated pits and caveolae as well as lipid metabolism are regulated by and provide feedback to YAP/TAZ (74,75) . Thus, additional insight will be gained by experiments and models that explore the role of membrane trafficking, membrane surface roughness, and membrane lipid metabolism on regulating YAP/TAZ mechanotransduction.…”
Section: Discussionmentioning
confidence: 99%
“…Most cells use membrane trafficking to continually rework their plasma membrane through ruffles, folds, endoand exocytosis, and it has been suggested that cells sense and regulate their volume and surface area through plasma membrane tension (73) . Recent evidence suggests that plasma membrane domains such clathrin coated pits and caveolae as well as lipid metabolism are regulated by and provide feedback to YAP/TAZ (74,75) . Thus, additional insight will be gained by experiments and models that explore the role of membrane trafficking, membrane surface roughness, and membrane lipid metabolism on regulating YAP/TAZ mechanotransduction.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the clumping of actin stress fibers elicits nuclear translocation of the YAP/TAZ cytoplasmic complex. Once in the nucleus, these proteins act as transcriptional co-activators of genes involved in the regulation of cytoskeleton and FA constituents ( Figure 3 ) [ 116 ]. Accordingly, in what seems to be a clear feedforward positive loop, in various types of solid tumor, YAP causes matrix stiffness and fiber densification by increasing stromal deposition of collagen [ 117 ].…”
Section: Three-dimensional (3d) Ecm-mimicking Scaffolds: Sensing mentioning
confidence: 99%
“…Among the thousands of genes whose expression is modified upon reprogramming, many are directly or indirectly related to metabolism [ 5 , 6 , 115 ]. Our understanding of the role exerted by YAP/TAZ in regulating metabolism is rapidly expanding [ 116 ]. It is worth noting that not only may their activity be influenced by the cellular metabolic status, but they are also able to promote a metabolic remodeling process, which may accompany cellular adaptation to changes in the environmental conditions ( Figure 2 ).…”
Section: Yap and Taz Are Modulators Of Metabolic Reprogrammingmentioning
confidence: 99%
“…YAP and TAZ are now recognized to reprogram cellular metabolic pathways, allowing cells to adapt to mutable environmental conditions [ 116 , 126 ]. They integrate physiological and environmental signals by modulating transcriptional programs to regulate the expression of metabolic enzymes and nutrient transporters.…”
Section: Yap and Taz Are Modulators Of Metabolic Reprogrammingmentioning
confidence: 99%